High cost or frequent attender - both spend resources, but are they linked to work disability? A cohort study from occupational health primary care in Finland - Tiia T. M. Reho; Salla A. Atkins; Nina Talola; Markku P. T. Sumanen; Mervi Viljamaa; Jukka Uitti (BMC, 2020)
Abstract Background High use of services is associated with ill health and a number of health problems, but more information is needed on whether high use of services presents a risk for future pensions or disability. We aimed to investigate if defining patients as high cost (HC) or frequent attenders (FA) was more useful in occupational health services (OHS) as a predictor of future disability pension (DP). Methods This cohort study used medical record data from a large OHS provider and combined it with register data from the Finnish Centre for Pensions including disability pension decisions. A total of 31,960 patients were included and odds ratios for DP were calculated. Frequent attenders (FA10) were defined as the top decile of visitors according to attendance and high cost (HC10) as the top decile according to costs accrued from service use in 2015. Those patients that were not categorized as FA nor HC, but were eligible for the study were used as the control group (non-FAHC). The outcome measure (disability pensions) was analysed for years 2016-2017. Results FA and HC did not significantly differ in their risk for disability pension. Both groups' risk was higher than average users' risk (adjusted OR 3.47 for FA10, OR 2.49 for HC10 and OR 0.33 for controls). Both HC10 and FA10 received half of their disability pensions based on musculoskeletal disorders, while for non-FAHC only 28% of pensions were granted based on these disorders. The groups overlapped by 68%. Conclusions High utilizers (both FA10 and HC10) have an increased likelihood of receiving a future disability pension. The chosen definition is less important than identifying these patients and directing them towards necessary rehabilitation.